The Influence of DPD Candidates and Political Trust in the General Elections Commission (KPU) on Voter Behavior during the DPD Re-Voting Election in Sangir District, South Solok Regency - Ebsyar, Iqbal Syafira; Adnan, M. Fachri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study examines the influence of DPD candidates and political trust in the General Elections Commission (KPU) on community voting behavior during the re-voting election (Pemungutan Suara Ulang/PSU) for the Regional Representative Council (DPD) of West Sumatra Province in Sangir District, South Solok Regency. The re-voting election was conducted based on the Constitutional Court Decision Number 03-03/PHPU.DPD-XXII/2024, which mandated a re-election due to procedural errors committed by the KPU in compiling the Final Candidate List (Daftar Calon Tetap/DCT). This study employed an associative quantitative approach. Data were collected through questionnaires using a four-point Likert scale and analyzed using multinomial logistic regression. The sample consisted of 100 respondents registered in the Permanent Voter List (Daftar Pemilih Tetap/DPT) in Sangir District and selected through simple random sampling. The results indicate that the candidate variable (X1) does not have a significant effect on voting behavior (Chi-Square = 2.271; p = 0.943). Political trust in the KPU (X2) also does not have a significant effect (Chi-Square = 7.439; p = 0.385). Simultaneously, both variables do not significantly influence voting behavior (p = 0.271). The Nagelkerke R² value of 0.157 indicates that the model explains 15.7% of the variation in voting behavior.